Insights into comparative genomics, structural features, and phylogenetic relationship of species from Eurasian Aster and its related genera (Asteraceae: Astereae) based on complete chloroplast genome - Chen, Hui; Li, Tingyu; Chen, Xinyu; Qu, Tianmeng; Zheng, Xinyi; Luo, Junjia; Li, Bo; Zhang, Guojin; Fu, Zhixi (Frontiers in Plant Science, 2024)
Aster L. is an economically and phylogenetically important genus in the tribe Astereae. Here, the complete plastomes of eight Aster species were assembled and characterized using next-generation sequencing datasets. The results indicated the complete plastomes of Aster had a quadripartite structure. These genomes were 152,045-152,729 bp in length and contained 132-133 genes, including 87 protein-coding genes, 37-38 tRNA genes, and 8 rRNA genes. Expansion or contraction of IR regions and forward, palindromic, complement, and reverse repeats were detected in the eight Aster species. Additionally, our analyses showed the richest type of SSRs was A/T mononucleotides, and 14 highly variable regions were discovered by analyzing the border regions, sequence divergence, and hot spots. Phylogenetic analyses indicated 27 species in Astereae were clustered into six clades, i.e., A-D, North American, and outgroup clades, and supported the genera Heteropappus, Kalimeris, and Heteroplexis are nested within Aster. The results indicated the clades B-D might be considered as genera. Divergence time estimate showed the clades A, B, C and D diverged at 23.15 Mya, 15.13 Mya, 24.29 Mya, and 21.66 Mya, respectively. These results shed light on the phylogenetic relationships of Aster and provided new information on specie identification of Aster and its related genera.